2014
DOI: 10.1177/0961203314559632
|View full text |Cite
|
Sign up to set email alerts
|

Eltrombopag as steroid sparing therapy for immune thrombocytopenic purpura in systemic lupus erythematosus

Abstract: Eltrombopag is effective as a rapidly acting corticosteroid sparing therapy for patients with ITP associated with SLE. This is important in reducing corticosteroid related side effects and morbidities in treating SLE patients with ITP. Larger studies are needed to ascertain safety and efficacy of eltrombopag in SLE patients with ITP, particularly those with coexisting antiphospholipid antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…There are very few reported cases of ITP secondary to autoimmune disorders successfully treated with THPO-RAs. (Gonzalez-Nieto et al, 2011;Alkaabi et al, 2012;Ruiz-Arguelles et al, 2013;Magnano et al, 2014;Scheinberg et al, 2014;Chang & Shih, 2015;Maroun et al, 2015) Here we report an excellent response in ITP secondary to autoimmune disorders. Similarly, the response rate in ITP secondary to infectious disorders was excellent.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…There are very few reported cases of ITP secondary to autoimmune disorders successfully treated with THPO-RAs. (Gonzalez-Nieto et al, 2011;Alkaabi et al, 2012;Ruiz-Arguelles et al, 2013;Magnano et al, 2014;Scheinberg et al, 2014;Chang & Shih, 2015;Maroun et al, 2015) Here we report an excellent response in ITP secondary to autoimmune disorders. Similarly, the response rate in ITP secondary to infectious disorders was excellent.…”
Section: Discussionsupporting
confidence: 58%
“…Also, eltrombopag is currently approved by the US Food and Drug Administration and the European Medicines Agency for the treatment of thrombocytopenia secondary to aplastic anaemia (Olnes et al, 2012) and thrombocytopenia secondary to hepatitis C infection (McHutchison et al, 2007;Afdhal et al, 2012). Eltrombopag has also been successfully used in a very small number of patients with immune thrombocytopenia secondary to chronic lymphatic leukaemia (Koehrer et al, 2010;Sinisalo et al, 2011;Gudbrandsdottir et al, 2012;Jolliffe & Romeril, 2014;Chang & Shih, 2015), systemic lupus erythematosus (SLE: Chang & Shih, 2015;Gonzalez-Nieto et al, 2011;Alkaabi et al, 2012;Scheinberg et al, 2014;Magnano et al, 2014;Maroun et al, 2015), Evans syndrome (Gonzalez-Nieto et al, 2011;Alkaabi et al, 2012;Ruiz-Arguelles et al, 2013;Magnano et al, 2014;Scheinberg et al, 2014;Chang & Shih, 2015;Maroun et al, 2015), human immunodeficiency virus (Quach et al, 2012;Aslam et al, 2014;Chang & Shih, 2015;Kowalczyk et al, 2015) and coeliac disease (Chang & Shih, 2015) who had a loss of response to standard treatment for ITP. The communication of such cases is essential to support the potential utility of eltrombopag as salvage therapy in the treatment of secondary immune thrombocytopenia.…”
mentioning
confidence: 99%
“…Many patients with ITP or secondary ITP due to lymphoproliferative disorders responding to eltrombopag have already been reported, but the efficacy of this drug for thrombocytopenia associated with SLE remains unclear, and only three reports have been published [ 3 5 ]. Maroun et al reported 3 SLE patients with thrombocytopenia refractory to glucocorticoids, in whom elevation of the platelet count was achieved by administration of eltrombopag.…”
Section: Discussionmentioning
confidence: 99%
“…76 Contrasting to these results a young SLE patient developed thrombotic microangiopathy with renal failure after romiplostim therapy. 77 Maroun et al 78 reported on three patients with SLE thrombocytopenia in which administration of eltrombopag was successful as steroid-sparing treatment. Another patient with refractory thrombocytopenia achieved a complete response after eltrombopag treatment.…”
Section: Thrombopoietin Receptor Agonistsmentioning
confidence: 99%